2012
DOI: 10.1038/nature11648
|View full text |Cite
|
Sign up to set email alerts
|

The TEL patch of telomere protein TPP1 mediates telomerase recruitment and processivity

Abstract: Human chromosome ends are capped by shelterin, a protein complex that protects the natural ends from being recognized as sites of DNA damage and also regulates the telomere-replicating enzyme, telomerase1–3. Shelterin includes the heterodimeric POT1-TPP1 protein, which binds the telomeric single-stranded DNA tail4–9. TPP1 has been implicated both in recruiting telomerase to telomeres and in stimulating telomerase processivity (the addition of multiple DNA repeats after a single primer-binding event)9–14. Deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

33
453
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 317 publications
(489 citation statements)
references
References 33 publications
33
453
1
2
Order By: Relevance
“…This interaction depends on the OB fold of TPP1 (15)(16)(17)(18)20). Recent studies have identified the residues that are required for the interface of TPP1-telomerase interaction (20)(21)(22). Our results thus far support the model that phosphorylation of S111 increases the telomerase activity that complexes with TPP1.…”
Section: Phosphorylation Of Tpp1 S111 Is Implicated In Telomere Lengthsupporting
confidence: 79%
See 2 more Smart Citations
“…This interaction depends on the OB fold of TPP1 (15)(16)(17)(18)20). Recent studies have identified the residues that are required for the interface of TPP1-telomerase interaction (20)(21)(22). Our results thus far support the model that phosphorylation of S111 increases the telomerase activity that complexes with TPP1.…”
Section: Phosphorylation Of Tpp1 S111 Is Implicated In Telomere Lengthsupporting
confidence: 79%
“…4A). Consistent with previous reports (20)(21)(22), several of the residues that are required for the interface of TPP1-telomerase interaction, including D166, E168, E169, E171, and E215, reside on the same face of the TPP1 3D structure (Fig. 4A).…”
Section: Phosphorylation Of Tpp1 S111 Is Implicated In Telomere Lengthsupporting
confidence: 78%
See 1 more Smart Citation
“…[18][19][20][21][22][23] We examined its role on hTERT-mediated telomere shortening. TPP1 knockdown did not affect average TL in SAOS2 (P = 0.72) and had no significant effect on the length of very long telomeres on 11q (Fig.…”
Section: Upregulation Of Endogenous Htert Maintains Small Tlv In Primmentioning
confidence: 99%
“…Together with RAP1 and the TIN2 and TPP1 proteins, which bridge TRF1 and TRF2 to POT1, the telomeric-DNA-binding proteins create a network of complexes that block DNA damage response activation (14). Interestingly, TPP1 also interacts with telomerase as an essential step of recruitment in a manner physiologically restricted to S phase of the cell cycle (12,(16)(17)(18)(19). In fission yeast, the dsDNA-binding protein Taz1 takes the place of TRF1 and TRF2, Pot1 binds to the single-stranded DNA overhang, and Rap1, Poz1, and Tpz1 function as bridging proteins that link Taz1 to Pot1 (20,21).…”
mentioning
confidence: 99%